Evaluación de la biodegradación de un insecticida piretroide en muestras de suelo de cultivo de papa mediante la adición de Trichoderma harzianum y Pleurotus ostreatus - Torres Granda, Evelyn Gabriela (2017)
The experiment was carried out in “San Fernando de Guamaní”, Quito, with the objective of evaluating the biodegradation of a pyrethroid insecticide in potato soil samples by the addition of T. harzianum and P. ostreatus. The field consisted in georeferencing the sampling site in the “El Capulí” sector in the province of Carchi and obtaining soil samples. P. ostreatus seed was obtained in Calacalí. In the laboratory phase, the analysis and quantification of the pyrethroid were performed in the soil samples (at the beginning and at the end of the test); In this phase also the isolation, massification and obtaining of the inoculum of each one of the fungic species was realized. The experimental design was based on a DCA with 4 replicates and 4 treatments, T0 (control); T1 (soil + T. harzianum + pyrethroid); T2 (soil + P. ostreatus + pyrethroid), T3 (soil + T. harzianum + P. ostreatus + pyrethroid). The variables studied were temperature, humidity, pH and electrical conductivity. T3 had a biodegradation percentage of 92.57%, surpassing the rest of the treatments. The results presented in this research show that T. harzianum and P. ostreatus are able to biodegrade the pyrethroid insecticide, confirming its potential and effective application, therefore, bioremediation is an excellent alternative in contaminant degradation processes.